2018
DOI: 10.1016/j.molmet.2018.02.001
|View full text |Cite
|
Sign up to set email alerts
|

Evidence against a role for NLRP3-driven islet inflammation in db/db mice

Abstract: ObjectivesType 2 diabetes (T2D) is associated with chronic, low grade inflammation. Activation of the NLRP3 inflammasome and secretion of its target interleukin-1β (IL-1β) have been implicated in pancreatic β cell failure in T2D. Specific targeting of the NLRP3 inflammasome to prevent pancreatic β cell death could allow for selective T2D treatment without compromising all IL-1β-associated immune responses. We hypothesized that treating a mouse model of T2D with MCC950, a compound that specifically inhibits NLR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
17
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(22 citation statements)
references
References 47 publications
5
17
0
Order By: Relevance
“…It is entirely possible that islet macrophages exhibit a ''mixed'' pro-inflammatory and reparative phenotype in type 2 diabetes in response to phagocytosis of dead beta-cells following cell death induced by IAPP and other factors (glucose, free fatty acids, endoplasmic reticulum stress, local and/or circulating cytokines). Regardless, our findings are in agreement with a recent study in db/db mice, wherein an NLRP3 inhibitor had no effects on glycemia (Kammoun et al, 2018). Ying and colleagues also found a mixed phenotype of islet macrophages during HFD feeding, not simply defined by M1 or M2 skewing (Ying et al, 2018).…”
Section: Discussionsupporting
confidence: 93%
“…It is entirely possible that islet macrophages exhibit a ''mixed'' pro-inflammatory and reparative phenotype in type 2 diabetes in response to phagocytosis of dead beta-cells following cell death induced by IAPP and other factors (glucose, free fatty acids, endoplasmic reticulum stress, local and/or circulating cytokines). Regardless, our findings are in agreement with a recent study in db/db mice, wherein an NLRP3 inhibitor had no effects on glycemia (Kammoun et al, 2018). Ying and colleagues also found a mixed phenotype of islet macrophages during HFD feeding, not simply defined by M1 or M2 skewing (Ying et al, 2018).…”
Section: Discussionsupporting
confidence: 93%
“…We also cannot exclude the possibility that differences in the gut microbiota may have contributed to this discrepancy, since the db/db mice in these two studies were derived from different sources. In support of our findings, a more recent study found that a potent inhibitor of NLRP3-induced IL-1β secretion had no effect on db/db disease pathogenesis (Kammoun et al, 2018). In any case, our data provide new insight into the functional state of islet macrophages in diabetes and during beta-cell death.…”
Section: Discussionsupporting
confidence: 90%
“…This impaired wound healing is observed when comparing WT mice to Ob/Ob mice, where WT mice heal within seven days and Ob/Ob mice take up to two weeks to heal wounds of the same size [ 18 ]. MCC950 has been previously described to have no effect on obesity or diabetes in a model of db/db diabetic mice [ 19 ]. Therefore, to study the effects of inflammasome-driven inflammation in chronic wound healing, the db/db model seemed ideal to test the effects of MCC950 on diabetic wounds, without affecting the diabetic phenotype itself.…”
Section: Discussionmentioning
confidence: 99%